2007
DOI: 10.1007/s11365-007-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Are government-linked IPOs underpriced? A three country privatization effort comparison

Abstract: Underpricing in the case of the initial public offerings of private (nongovernment) firms has been well documented. However, there does not appear to be any systematic study of the price performance of "government-linked" companies or GLCs, which have been "privatized" through public offerings in the stock market. This study examines the hypothesis that the initial public offerings (IPOs) of such companies in the United Kingdom, Singapore, and Malaysia will not only be underpriced, but their degree of underpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Typically, it has been thought that the key factors for success in network markets are the pricing policy adopted (Ariff, Prasad, & Vozikis, 2007;Brynjolfsson & Kemerer, 1996;Dhebar & Oren, 1986;Katz & Shapiro, 1986;Oren & Dhebar, 1985;Sanchis, 2006;Xie & Sirbu, 1995), the expectations of success generated (Balacer & Lippman, 1984;Besen & Farrell, 1994;Economides, 1996aEconomides, , 1996bEconomides & Himmelberg, 1995a, 1995bKatz & Shapiro, 1985, 1992Mas-Verdú, 2007;McGee & Sammut, 2002;McKee, 2008;Yang, 1997), the complementary products market (Amit & Zott, 2001;Brynjolfsson & Kemerer, 1996;Colombo & Grilli, 2006;Cusumano, Mylonadis, & Rosenbloom, 1992;Gupta, Jain, & Sawheny, 1999;Nelson, Kanso, & Levitt, 2007;Shapiro & Varian, 1998, 1999Wade, 1995), or the moment of entry into the market (Schilling, 1998(Schilling, , 2002Srinivasan, Lilien, & Rangaswamy, 2004). We know now that the market structure itself must also be taken into consideration: the evolution of the latter will vary widely depending on the public targeted by marketing actions during the launch phase.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it has been thought that the key factors for success in network markets are the pricing policy adopted (Ariff, Prasad, & Vozikis, 2007;Brynjolfsson & Kemerer, 1996;Dhebar & Oren, 1986;Katz & Shapiro, 1986;Oren & Dhebar, 1985;Sanchis, 2006;Xie & Sirbu, 1995), the expectations of success generated (Balacer & Lippman, 1984;Besen & Farrell, 1994;Economides, 1996aEconomides, , 1996bEconomides & Himmelberg, 1995a, 1995bKatz & Shapiro, 1985, 1992Mas-Verdú, 2007;McGee & Sammut, 2002;McKee, 2008;Yang, 1997), the complementary products market (Amit & Zott, 2001;Brynjolfsson & Kemerer, 1996;Colombo & Grilli, 2006;Cusumano, Mylonadis, & Rosenbloom, 1992;Gupta, Jain, & Sawheny, 1999;Nelson, Kanso, & Levitt, 2007;Shapiro & Varian, 1998, 1999Wade, 1995), or the moment of entry into the market (Schilling, 1998(Schilling, , 2002Srinivasan, Lilien, & Rangaswamy, 2004). We know now that the market structure itself must also be taken into consideration: the evolution of the latter will vary widely depending on the public targeted by marketing actions during the launch phase.…”
Section: Discussionmentioning
confidence: 99%
“…Literature abounds on strategies for local development and actions carried out in this area aimed at favouring social and working integration policies, particularly for socially disadvantaged groups or those with a greater risk of exclusion (Sachs 1980;Stöhr 1990;Fosler 1991;Bennet 1991;Blakely 1994;Ward, Lowe and Bridges 2003;Iyer, Kitson and Toh 2005;Blackburn and Ram 2006), as well as on the management of projects in this area (Gunton 2003;Acs and Storey 2004). However, and despite the fact that the context in which LDEOs must carry out their work is, in many cases, not the most appropriate and that a good deal of their actions are the result of or are supported by political decisions (from local administrations) (Sanchis and Cantarero 1999;FOREM 2000;Colombo and Grilli 2006;Ariff, Prasad and Vozikis 2007), to date, no study has been carried out that attempts to analyse which factors might be essential in ensuring the success of these actions.…”
Section: Links Between the Determining Factors In The Success Of Orgamentioning
confidence: 99%
“…Of course, they, as the shareholders, would benefit from the value created by such investments. In some cases, it was reported that the investments were not made.12 That is, one day after the share issues, the Malaysian shares were worth 134 percent more and the Singapore shares were worth 42 percent more(Ariff et al 2007).…”
mentioning
confidence: 99%